1980
DOI: 10.1017/s0033291700044147
|View full text |Cite
|
Sign up to set email alerts
|

Meditation and the EEG

Abstract: SYNOPSIS Previous research on meditation and the EEG is described, and findings relating to EEG patterns during meditation are discussed. Comparisons of meditation with other altered states are reviewed and it is concluded that, on the basis of existing EEG evidence, there is some reason for differentiating between meditation and drowsing. Research on alpha-blocking and habituation of the blocking response during meditation is reviewed, and the effects of meditation on EEG patterns outside of meditation are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…The existing research on the acute CNS effects of RT suggests that RT such as meditation result in alterations in CNS arousal as measured by acute changes in alpha or theta EEG activity in experienced practitioners (Delmonte, 1984;West, 1980). Although many studies have reported increased alpha activity during RT, others have reported decreased alpha (Jacobs & Lubar, 1989;Stigsby, Rodenburg, & Moth, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The existing research on the acute CNS effects of RT suggests that RT such as meditation result in alterations in CNS arousal as measured by acute changes in alpha or theta EEG activity in experienced practitioners (Delmonte, 1984;West, 1980). Although many studies have reported increased alpha activity during RT, others have reported decreased alpha (Jacobs & Lubar, 1989;Stigsby, Rodenburg, & Moth, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…A number of papers have reported the EEG findings for experimental subjects under meditation [3]- [5] [8]- [12]. EEG has been recognized to be an important clinical tool for diagnosing and monitoring the nervous system [13]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…EEG has been recognized to be an important clinical tool for diagnosing and monitoring the nervous system [13]- [15]. In the meditation EEG study, West [5] summarized the EEG findings and made three major comments including: slower alpha with larger power at the meditating beginning, occurrence of the rhythmic theta trains for experienced meditators at the mid session, and very rarely, bursts of high-frequency beta (above 20Hz) observed for in biomedical signal processing [16]- [20]. Appropriate selection of scales and wavelet bases enables it to characterize the EEG rhythmic patterns [20]- [22].…”
Section: Introductionmentioning
confidence: 99%
“…The research on the CNS effects of the RR that has been done suggests that the RR results in reductions in CNS arousal as measured by increases in alpha or theta EEG activity (Delmonte, 1984;West, 1980). However, this research has been hampered by a number of methodological problems, including lack of empirically sound experimental designs (self-selection bias, nonrandom assignment, no pretesting prior to training), reliance on visual analyses of a few channels of EEG activity, and failure to assess CNS effects in novice subjects to determine if the CNS effects of the RR are immediate.…”
mentioning
confidence: 99%